2019
DOI: 10.1186/s13000-019-0848-7
|View full text |Cite
|
Sign up to set email alerts
|

Triple malignancy (NET, GIST and pheochromocytoma) as a first manifestation of neurofibromatosis type-1 in an adult patient

Abstract: Background Neurofibromatosis type-1 (NF1), also called von Recklinghausen disease, is a rare genetic disease which can lead to the development of benign or even malignant tumors. NF1 is mostly diagnosed in children or early adolescents who present with clinical symptoms. A curative therapy is still missing and the management of NF1 is based on careful surveillance. Concerning tumors which affect the gastrointestinal tract in patients with NF1, the most common is a gastrointestinal stromal tumor (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
(19 reference statements)
1
14
0
Order By: Relevance
“…A review of patients with neuroendocrine tumors and NF1 found pheochromocytoma in 6/27 (22%), suggesting a possible link [ 41 ]. The co-existence of all 3 neoplasms (neuroendocrine tumor, pheochromocytoma, GIST) in NF1, such as in this report, is exceedingly rare, but has been reported previously [ 42 ]. Whether there is an underlying association or common mechanism between these malignancies is unknown; however, discovery of a neuroendocrine tumor in a patient with NF1 should prompt investigation of other potential neoplasms.…”
Section: Discussionsupporting
confidence: 60%
“…A review of patients with neuroendocrine tumors and NF1 found pheochromocytoma in 6/27 (22%), suggesting a possible link [ 41 ]. The co-existence of all 3 neoplasms (neuroendocrine tumor, pheochromocytoma, GIST) in NF1, such as in this report, is exceedingly rare, but has been reported previously [ 42 ]. Whether there is an underlying association or common mechanism between these malignancies is unknown; however, discovery of a neuroendocrine tumor in a patient with NF1 should prompt investigation of other potential neoplasms.…”
Section: Discussionsupporting
confidence: 60%
“…NET and GIST have been reported to be diagnosed simultaneously in the case of neurofibromatosis type 1, but it is known that they are extremely rare in patients with no genetic diseases, as in this case. 23,24 Of the previous reports regarding the simultaneous occurrence of GIST and NET in the gastrointestinal tract, we achieved to retrieve data only for four cases. Two cases were diagnosed in patients without complaints and the others were diagnosed in patients with symptoms such as melena or abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…GIST, carcinoid tumors and other NETs are frequently reported in NF1 patients and they are considered part of the NF1 tumor spectrum, occurring in isolated manifestation or, in rare events, in synchronism with other tumors (Sørensen et al, 1986;Kim et al, 2014;Park et al, 2019). The co-occurrence of periampullary NET tumors and GIST has been proposed as highly suggestive or even pathognomonic of NF1 (Agaimy et al, 2012;Park et al, 2019;Poredska et al, 2019). LOH is a common event for the development of malignancies in NF1 patients, and has been considered by some as a prerequisite to cancer occurrence (Ruggieri and Packer, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In this report, the patient was diagnosed with multiple tumors (GIST, NET of the minor ampulla, and adenocarcinoma of the major ampulla), of which GIST and NET are likely related to NF1, a diagnosis confirmed by germline genetic testing. Among the tumors identified, GIST represents the most common gastrointestinal tumor in NF1 patients (Poredska et al, 2019), accounting for 5 to 25% of all NF1 neoplasms (Zöller et al, 1997;Miettinen et al, 2006). The last update of duodenal and periampullary tumors in NF1 patients indicates that most (60%) neoplasms arise in the duodenum, while 31% originate in the ampulla of Vater.…”
Section: Discussionmentioning
confidence: 99%